Der Wiener Studentenverein "Bar Giora" und sein Einfluss auf die Entstehungsgeschichte des Zionismus im kroatischen und südosteuropäischen Raum des Habsburgerreiches = The Viennese Student Association "Bar Giora" and its Influence on the Genesis of Zionism in the Croatian and Southeast European Areas of the Habsburg Empire - Bitunjac, Martina (Aschkenas, 2021)
The establishment of the Bar Giora Zionist student association at the University of Vienna in 1904 was an important factor in the development of Zionism in the territory of the former Yugoslavia. The Verein jüdischer Akademiker aus den südslavischen Ländern (Association of Jewish Alumni from the South Slavic Countries) and its committed members had great influence on the transfer of the idea of a Jewish nation-state to the South Slavic region by creating multicultural supra-regional networks, organising conferences and publishing nationally oriented journals. The young Zionists from the Balkans also faced strong criticism from assimilated Jews. This paper explores the origins of Bar Giora, its self-understanding and its impact, as well as the assimilationist challenges faced by the Zionists.